Supporting Firms in Restructuring and Recovery - World Bank Group (World Bank, Washington, DC, 2021)
Firms and workers continue to be deeply affected by COVID-19, while the reach of policy support has been limited. Only one in four businesses surveyed across 60 countries has received any type of public support, with the share varying from more than 50 percent in high-income countries to just over 10 percent for low-income economies. The rest of this note is structured as follows. The next section presents the main impacts of COVID-19 on businesses. Section three revisits the organizing framework of the first Supporting Firm Resilience note (Freund and Mora 2020), reaffirming its relevance as the underlying methodology for analysis and guide to policy discussions with client authorities. Section four summarizes the policy responses by authorities around the world. Section five provides some early evidence on the impact of policies as well as recommendations for improving their targeting and effectiveness. Section six maps out the way forward for countries. Section seven concludes and outlines how the WBG can support.